Low-Cost Open-Source Device to Measure Maximal Inspiratory and Expiratory Pressures - Aymerich, Claudia; Rodríguez-Lázaro, Miguel; Solana, Gorka; Farré, Ramon; Otero, Jorge (Frontiers in Physiology, 2021)
ABSTRACT Measurement of maximal inspiratory (MIP) and expiratory (MEP) pressures is a widely used technique to non-invasively evaluate respiratory muscle strength in clinical practice. Commercial devices that perform this test range from whole body plethysmographs to portable spirometers, both expensive and including a wide range of other respiratory tests. Given that a portable, low-cost and specific option for MIP and MEP measuring device is not currently right now in the market, a high-performance and easy-to-build prototype has been developed and the detailed technical information to easily reproduce it is freely released. The novel device is based on an Arduino microcontroller with a digital display, an integrated pressure transducer, and 3D printed enclosure (total retail cost 80 €). The validation of the device was performed by comparison with a laboratory reference setting, and results showed an accuracy within ±1%. As the device design is available according to the open source hardware approach, measuring MIP/MEP can greatly facilitate easily available point-of-care devices for patient’s monitoring and, most important, for making this lung function measurement tool affordable to user in low- and middle-income countries.